2021
DOI: 10.1016/j.jhep.2020.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Association of liver abnormalities with in-hospital mortality in patients with COVID-19

Abstract: Background and Aims The evolution and clinical significance of abnormal liver chemistries and the impact of hepatitis B infection on outcome in patients with COVID-19 is not well characterized. This study aimed to explore these issues. Methods This large retrospective cohort study included 2073 patients with COVID-19 having definite outcomes in Wuhan, China. Longitudinal liver function tests were conducted and determined their associated factors and death risk by multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
143
2
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(164 citation statements)
references
References 19 publications
(16 reference statements)
15
143
2
4
Order By: Relevance
“…The prognostic significance of elevated liver enzymes in patients infected with SARS-CoV-2 is currently debated. Some reports have demonstrated that elevations of serum liver enzyme levels are associated with adverse outcomes, including shock, intensive care unit (ICU) admission and mechanical ventilation 43 , 65 , 71 74 . However, these studies could be prone to bias if patients with severe disease received more intensive laboratory monitoring, increasing the likelihood of detecting liver injury.…”
Section: Liver Biochemistry In Covid-19mentioning
confidence: 99%
“…The prognostic significance of elevated liver enzymes in patients infected with SARS-CoV-2 is currently debated. Some reports have demonstrated that elevations of serum liver enzyme levels are associated with adverse outcomes, including shock, intensive care unit (ICU) admission and mechanical ventilation 43 , 65 , 71 74 . However, these studies could be prone to bias if patients with severe disease received more intensive laboratory monitoring, increasing the likelihood of detecting liver injury.…”
Section: Liver Biochemistry In Covid-19mentioning
confidence: 99%
“…Therefore, it appears that the cytokine storm is one of the important defining fac- tors contributing to morbidity and mortality in those with liver disease. 54 A raised AST and direct bilirubin at baseline were independent predictors of COVID-19 mortality.…”
Section: Covid-19 Inflammation Coagulation and Liver Diseasementioning
confidence: 90%
“…After propensity matching, the baseline and peak values of liver function tests, the trajectory of COVID-19 and severity of liver scores and outcomes are often equivalent in those with compensated cirrhosis. 54,55 In contrast, in decompensated liver disease, there is a marked risk of COVID-19-associated liver and coagulation failure. Particularly, studies have reported such events in patients with Child-Turcotte-Pugh B and C cirrhosis with increased decompensation events like ascites, coagulopathy, and hepatic encephalopathy and inhospital mortality.…”
Section: Covid-19 Inflammation Coagulation and Liver Diseasementioning
confidence: 99%
“…Generally, on the basis of current data, many authors argue with weak evidence of a causal association between SARS-CoV-2 infection and obstetric complications, stating that further investigations are needed. Hypertension, kidney disease, thrombocytopenia or liver injury are frequently seen in moderate to severe COVID19 cases [ 205 , 206 , 210 , 211 ]. If they occur during pregnancy, patients could fulfill complete or incomplete clinical and/or laboratory PE or HELLP syndrome criteria [ 71 ].…”
Section: Covid-19 and Pregnancymentioning
confidence: 99%